Sandra Ingram

answers: 1

Register to add an answer

The time for answering the question is over

60 cents

Answer:

x+a is factor of x

4

−a

2

x

2

+3x−6a

Let p(x)=x

4

−a

2

x

2

+3x−6a

we know that if x−α is a factor of p(x) then p(α)=0

So p(−a)=0

(−a)

4

−a

2

(−a)

2

+3(−a)−a=0

a

4

−a

4

−3a−a=0

−4a=0

a=0

206

Polivanov

For answers need to register.

Contacts

mail@expertinstudy.com

Feedback

Expert in study

About us

For new users

For new experts

Terms and Conditions